Efektivitas Ekstrak Etanol Biji Alpukat (Persea americana Mill.) Terhadap Kadar Glukosa Darah Tikus Putih Jantan (Rattus Novergicus) Model Hiperkolesterolemia-Diabetes: Effectiveness of Ethanol Extract of Avocado Seeds (Persea americana mill.) on Blood Glucose Levels of Male White Rat (Rattus novergicus) Hipercolesterolemia-diabetes Model - Patala, Recky; Dewi, Niluh Puspita; Pasaribu, Meilinda Handayani (Universitas Tadulako, 2020)
Diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels due to a deficiency of insulin secretion or when insulin resistance occurs. Herbal medicine is one alternative method that can be used to control blood glucose levels and prevent complications of diabetes mellitus. One of the medicinal plants is avocado seeds (Persea americana Mill.) The active compounds contained in avocado seeds that have antidiabetic activity are flavonoids, alkaloids, tannins and saponins. This study aims to determine the content of secondary metabolites in the extract of avocado seed, the effect of extract of avocado seed and the dose of extract of avocado seed that is effective in lowering blood glucose levels. This research was a laboratory experiment using a modified randomized controlled pretest and posttest group design. Test animals used were 30 rats which were divided into six treatment groups, namely normal control, negative control, positive control, a dose of 250, 300 and 350 mg/kg groups. The results showed that extract of avocado seed contained secondary metabolites: flavonoids, alkaloids, saponins, and tanins;extract of avocado seed gave effect to decrease blood glucose levels; extract of avocado seed with a dose of 350 mg/kg was effective in lowering blood glucose levelswith an avarage decrease of 99,8 mg/dL.